GAMBARAN BAURAN PROMOSI UNIT PEMASARAN RUMAH SAKIT ISLAM SURABAYA - Prasasti Nur Rachmi (VISIKES: Jurnal Kesehatan Masyarakat, 2020)
In this globalization era, such activity of marketing for health service is highly needed to be undertaken. Supported by the advanced health technology, it is getting clearer that the business in this field has grown rapidly, so that each hospital is suggested to improve their utilization for the better service. There is one method that can be done by any hospitals to inform and communicate the offered health service which is promotion mix. This study purposes to know the conception of promotion mix that is done by an Islamic Hospital in Surabaya. Moreover, this study employs qualitative method along with observation and interview as the method of data sampling. This study was performed from August until October 2017. The data analysis used in this study is descriptive. Furthermore, the result of the study indicated that the practice of promotion mix in the Islamic Hospital in Surabaya had proceeded properly.Keywords: promotion mix, hospital, health promotion